T Cell Receptor Gene Therapy for Cancer - Thomas M. Schmitt; Gunnar B. Ragnarsson; Philip D. Greenberg (2009)
T cell-based adoptive immunotherapy has been shown to be a promising treatment for various types of cancer. However, adoptive T cell therapy currently requires the custom isolation and characterization of tumor-specific T cells from each patient—a process that can be not only difficult and time-consuming but also often fails to yield high-avidity T cells, which together have limited the broad application of this approach as a clinical treatment. Employing T cell receptor (TCR) gene therapy as a component of adoptive T cell therapy strategies can overcome many of these obstacles, allowing autologous T cells with a defined specificity to be generated in a much shorter time period. Initial studies using this approach have been hampered by a number of technical difficulties resulting in low TCR expression and acquisition of potentially problematic specificities due to mispairing of introduced TCR chains with endogenous TCR chains. The last several years have seen substantial progress in our understanding of the multiple facets of TCR gene therapy that will have to be properly orchestrated for this strategy to succeed. Here we outline the challenges of TCR gene therapy and the advances that have been made toward realizing the promise of this approach.